Review: Jeremy Waldron's Political Political Theory. (July 2019) - Runciman, David
This collection seeks to ground political theory in the study of institutions, particularly the constitutional relationship between different branches of government. It makes the case that 'constitutionalism' has become a thin doctrine of political restraint. Waldron wants to identify a fuller conceptual understanding of how the functions of government can be empowered and articulated. In doing so, he sets out a position that is distinct from both moralism and realism in contemporary political theory. I explore how well the later distinction holds up: how successfully does Waldron's approach marry realist concerns with the rigour of analytical political theory? I also discuss the role it leaves for the history of political thought and whether it can deal with the populist strain in contemporary politics.